Prevention of Hudood (Fixed punishments) on doubt and dispute over what is considered doubt and what is not - Muhammad Husni, Ahmad; Nasohah, Zaini; Mohd. Nor, Amir Husin; Samuri, Mohd Al-Adib; Mohamad, Abdul Basir; Laluddin, Hayatullah (American-Eurasian Network for Scientific Information (AENSI), 2013)
Hudood (Fixed punishments) and Qisas (Retribution) offenses are regarded as most dangerous crimes that are prevalent in Islamic Society. The government determines for each crime and the offender the type and amount of punishment. Amongst them there are crimes that do not accept intercession or waiver if there is no doubt or confusion in the case. In spite of that, the Shariah has established rules and regulations that would not allow the implementations of these punishments unless the crime can be proven beyond reasonable doubt and the crime deserves that particular punishment; this is because of the maxim “hudood are to be prevented when there are doubts”. The Islamic Jurists are unanimous on the said maxim which has a root from the sayings and actions of the Holy Prophet (saw) and also to that of his companions may Allah be pleased with them. The maxim is also connected to the Islamic Legal Maxims such as “A person is presumed innocent unless proven guilty” and “Certainty cannot disappear because of doubt”. The doubt may be related to pillars of the crime or evidence or surrounding circumstances. Thus, based on the saying “hudood are to be prevented when there are doubts”, it is for the judge to investigate and verify that the crime deserves the punishment; if it is proven that there is a doubt in the case either from one of its pillars or evidence, then the judge must do all he can to set aside the punishment and to mitigate it ‘ta’zir’ (Discretionary Penalty).